2020
DOI: 10.1111/jir.12716
|View full text |Cite
|
Sign up to set email alerts
|

Family members and health care workers' perspectives on motivational factors of participation in physical activity for people with intellectual disability: A qualitative study

Abstract: Background People with intellectual disabilities (ID) have lower levels of physical activity than the general population. The aim of this study was to understand the motivational factors of participation in physical activity for people with ID from the perspectives of the family members and staff. Method An abductive qualitative design was used. Social Cognitive Theory constituted the theoretical frame of reference of the study. Two focus group interviews with health care workers and family members and two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…This randomized controlled trial is part of our project to develop a tailored mHealth support system that promotes PA in individuals with IDs [ 38 ]. In previous parts of the project, we conducted a qualitative study on motivation for participation in PA for individuals with IDs [ 21 ], held workshops and collaborated with mHealth developers, and performed usability tests. This process is illustrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This randomized controlled trial is part of our project to develop a tailored mHealth support system that promotes PA in individuals with IDs [ 38 ]. In previous parts of the project, we conducted a qualitative study on motivation for participation in PA for individuals with IDs [ 21 ], held workshops and collaborated with mHealth developers, and performed usability tests. This process is illustrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Findings from previous studies indicate that a more flexible approach [ 19 ], greater use of theory in intervention design, stronger research design (as there are few randomized controlled studies), and better translation of interventions to community-based settings [ 20 ] are needed. Future studies could also have an ecological approach, where the interplay between individual, interpersonal, and environmental factors are considered [ 1 , 21 ]. Motivational issues have been challenging, particularly for approaches that aim for sustainable effects [ 17 ], and should be considered when designing future PA interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dixon-Ibarra [ 20 , 21 ] reported barriers (resident motivation, limited staff, negative support, and resident age) and facilitators (role modelling/encouraging, enjoyment). A recent qualitative study [ 22 ] focused on motivational factors of PA participation perceived by health care workers and family members; its findings suggested that engagement with contextual support is a prerequisite for higher motivation. Other research findings have indicated that the characteristics of the residents (e.g., physical and mental health, age, preference/motivation) could have impacted on the capability, motivation, and opportunity of the professional staff in rendering PA support for people with ID [ 16 ].…”
Section: Introductionmentioning
confidence: 99%